2015
DOI: 10.1017/s0033291715002019
|View full text |Cite
|
Sign up to set email alerts
|

Default mode network abnormalities during state switching in attention deficit hyperactivity disorder

Abstract: Background. Individuals with ADHD display excess levels of default mode network (DMN)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 64 publications
3
23
0
Order By: Relevance
“…The DMN has been demonstrated to be the most active during rest, and to deactivate during active task engagement [45]. In this study, there was a similar developmental trend in the ADHD and TD groups, i.e., that part of the FC in the DMN diminished with age.…”
Section: Discussionsupporting
confidence: 66%
“…The DMN has been demonstrated to be the most active during rest, and to deactivate during active task engagement [45]. In this study, there was a similar developmental trend in the ADHD and TD groups, i.e., that part of the FC in the DMN diminished with age.…”
Section: Discussionsupporting
confidence: 66%
“…Greater activity in the DAN in relation to ADHD (of which Rohr et al 20 inattention is one of the two main symptoms) has previously been shown and interpreted as compensatory effort (Cortese, et al, 2012). While several studies have reported increased DMN activity during tasks in ADHD vs. TD participants, (Sidlauskaite, et al, 2016) found that the process of down-regulating the DMN when preparing to switch from rest to task was unimpaired in ADHD. This is a somewhat counter-intuitive, as the ability to modulate or suppress DMN activity via the DAN is linked to greater top-down, goaldirected attention (Anticevic, et al, 2012;Rubia, 2013), which is an area of difficulty in ADHD.…”
Section: Discussionmentioning
confidence: 94%
“…More generally, Sidlauskaite et al (2016) question whether documented abnormalities in DMN suppression in ADHD are in fact reflecting difficulties in sustaining DMN suppression, as their study shows that initial DMN suppression when cued to execute a task is not impaired in ADHD. However, this hypothesized dysfunction in sustaining DMN suppression has yet to be explored in ADHD.…”
Section: Introductionmentioning
confidence: 97%